2021
DOI: 10.3390/ijerph18157953
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatigue, Quality of Life, Turnover Intention, and Safety Incident Frequency between 2-Shift and 3-Shift Korean Nurses

Abstract: This study aimed to compare the fatigue, quality of life, turnover intention, and safety incident frequency between 2- and 3-shift nurses, and analyze their perceptions of the 2-shift system. Participants were 227 nurses working for one year or more in a tertiary hospital in Seoul, South Korea (113 were 2-shift nurses for two months or longer, and 114 were 3-shift nurses with no experience of 2-shift work). The Occupational Fatigue Exhaustion Recovery Scale (OFER) and Quality of Life Scale were used. Turnover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Of interest, authors from the same study (Jarrar et al, 2019) found that shift length indirectly affects nurses' perceived medication error. Planned longer shifts, such as 12‐h shifts, appear to have less significance on the incidence of MAEs than unplanned overtime (Hong et al, 2021; Liu et al, 2012, Olds & Clarke, 2010; Wilkins & Shields, 2008). This has implications for nurse managers when developing rosters, as RNs working overtime is a factor which can be prevented and warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, authors from the same study (Jarrar et al, 2019) found that shift length indirectly affects nurses' perceived medication error. Planned longer shifts, such as 12‐h shifts, appear to have less significance on the incidence of MAEs than unplanned overtime (Hong et al, 2021; Liu et al, 2012, Olds & Clarke, 2010; Wilkins & Shields, 2008). This has implications for nurse managers when developing rosters, as RNs working overtime is a factor which can be prevented and warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors include role conflict, workload, lack of social support, control, community, rewards, fairness, values, and the level of flexibility of working time, while personal factors are gender, age, marital status, personality, and expectations (10,18,26). However, the different levels of fatigue across the included studies could be explained by different work environments such as different units/wards, shift work (28), and different workloads (10). Women suffer from higher burnout rates than men.…”
Section: Discussionmentioning
confidence: 99%
“…Shift work has been shown to cause circadian rhythm disturbances. As a result of sleep deprivation, shift workers are likely to experience disruption of daily life, which can lead to chronic illness, higher levels of fatigue harm to job satisfaction and quality of life (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that more and more employees are experiencing longer work hours, shorter recovery periods, and more unpredictability in terms of scheduling [ 7 ]. Organizational research has shown that these changes in work schedules have been accompanied by increases in employee fatigue, burnout, turnover, and other negative outcomes [ 8 ]. In addition, research on shiftwork over the past century has shown that shiftworkers experience higher levels of fatigue due to the non-circadian nature of their schedules [ 1 ].…”
Section: Introductionmentioning
confidence: 99%